2011
DOI: 10.1128/cvi.00080-11
|View full text |Cite
|
Sign up to set email alerts
|

Varying Effects of Different β-Glucans on the Maturation of Porcine Monocyte-Derived Dendritic Cells

Abstract: ␤-Glucans are well known for their immunomodulatory capacities in humans and mice. For this reason, together with the European ban on growth-promoting antibiotics, ␤-glucans are intensively used in pig feed. However, as shown in the present study, there is much variation in the stimulatory capacities of ␤-glucans from different sources. Since dendritic cells (DCs) are the first cells that are encountered after an antigen is taken up by the intestinal epithelial cell barrier, we decided to investigate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…It is known that various beta-glucan preparations have different effects on the immune system, where not only the size and the degree of branching are responsible but also the solubility [7,9,20]. One explanation could be the fact that for activation of the Dectin-1 receptor, whole beta-glucans are necessary, as shown very recently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that various beta-glucan preparations have different effects on the immune system, where not only the size and the degree of branching are responsible but also the solubility [7,9,20]. One explanation could be the fact that for activation of the Dectin-1 receptor, whole beta-glucans are necessary, as shown very recently.…”
Section: Discussionmentioning
confidence: 99%
“…Highly polymer betaglucans with a molecular weight of 100,000 Da -200,000 Da expressed the highest immune stimulating activity, whereas fractions of very short beta-glucans between 5000 Da -10,000 Da, extracted from the same organism, exhibited no activity [8]. Further investigations showed that particles with -(1,6) branching together with - (1,3) branching are more effective than -(1,3) branching alone [9]. It seems that at least for common cold prevention, soluble (1,3)-(1,4)--glucan prepared from oat is not effective [10].…”
Section: Introductionmentioning
confidence: 95%
“…However, impurities such as starch and soluble/insoluble dietary fibre, which are possibly present in these extracts, may affect cell responses. [].…”
Section: Discussionmentioning
confidence: 99%
“…This structural aspect could influence the cell migration. Glucans, particular β-glucans in which the J3 fraction is rich, are able to act into the maturation of monocyte-derivatives dendritic cells as well as macrophage chemotactic recall into skin damage, both wound and surgical cut [36,37]. Furthermore, it is worth noting that only recently, four types of β-glucans extracted from different cereals promote epithelial cell migration.…”
Section: Scratch Assaymentioning
confidence: 99%